Indian Ethos In the Poetry of T.S. Eliot: The Influence of Indian Wisdom on T.S. Eliot's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thehoary Indian wisdom has attracted many intellectuals in the West. With thegrowth of Indology in England and Germany, Europe turned to the East. Duringthe mid nineteenth century, Emerson, Thoreau, and Whitman had begun publishingpoems, essays and books containing oriental colourings. In those days, Harvardhad become a famous centre for oriental studies. T.S. Eliot among others,studied there from 1906 to 1914. In those days, he came in contact with hislearned Gurus like Charles R. Lanman and James H. Woods, who themselves were busyin reading and anthologizing books related to Hinduism. T.S. Eliot presentedthe credentials of a wide range  ofpoetic sensibility by incorporating in his poetry not only the best of Europeanculture and American mind but also of Indian thought and tradition.